2021
DOI: 10.1101/2021.01.08.425839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dimerisation of the PICTS complex via LC8/Cut-up drives co-transcriptional transposon silencing inDrosophila

Abstract: In animal gonads, the PIWI-interacting RNA (piRNA) pathway guards genome integrity in part through the co-transcriptional gene silencing of transposon insertions. In Drosophila ovaries, piRNA-loaded Piwi detects nascent transposon transcripts and instructs heterochromatin formation through the Panoramix-induced co-transcriptional silencing (PICTS) complex, containing Panoramix, Nxf2 and Nxt1. Here, we report that the highly conserved dynein light chain LC8/Cut-up (Ctp) is an essential component of the PICTS co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
(194 reference statements)
0
5
0
Order By: Relevance
“…Within the nucleus, Piwi–piRNA functions together with Panx‐Nxf2‐p15 at the nascent transcript, in order to silence target TEs (Batki et al , 2019; Fabry et al , 2019; Murano et al , 2019; Zhao et al , 2019). Recent studies have suggested that Panx‐Nxf2‐p15 complex forms condensates upon Piwi–piRNA‐mediated silencing (Eastwood et al , 2021; Schnabl et al , 2021). Condensate formation is coupled to dimerization of Panx‐Nxf2‐p15 complex, and piRNA target regions may therefore be spatially regulated upon silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the nucleus, Piwi–piRNA functions together with Panx‐Nxf2‐p15 at the nascent transcript, in order to silence target TEs (Batki et al , 2019; Fabry et al , 2019; Murano et al , 2019; Zhao et al , 2019). Recent studies have suggested that Panx‐Nxf2‐p15 complex forms condensates upon Piwi–piRNA‐mediated silencing (Eastwood et al , 2021; Schnabl et al , 2021). Condensate formation is coupled to dimerization of Panx‐Nxf2‐p15 complex, and piRNA target regions may therefore be spatially regulated upon silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, whether Piwi–piRNA and its silencing complex, which associate with nascent RNA rather than chromatin, regulate chromatin conformation to trigger heterochromatin formation is unknown. Recent studies indicate that silencing complexes formed by Panx–Nxf2–p15 further associate with the dynein light chain protein, LC8, and form condensates in a dimer‐dependent manner to induce co‐transcriptional silencing (Eastwood et al , 2021; Schnabl et al , 2021). However, whether Piwi–piRNA regulation impacts nuclear spatial organization in vivo is still unrevealed.…”
Section: Introductionmentioning
confidence: 99%
“…4A and B). Next, using RNA-seq data from ovarian somatic cells (OSCs) (GSE160860) (41), we further filtered the soma-enriched genes that are highly expressed in OSCs.…”
Section: Germ Cell-specific Genes Show Rapid Evolution Of Promoters A...mentioning
confidence: 99%
“…To stringently define the germline genes, we additionally used processed RNA-seq data from early fly embryos (0-2hr, modENCODE; mRNA-seq fly embryo 0-2hr; RPKM; mE_mRNA_em0-2hr; FBlc0000086) to further filter the germline-enriched genes using >9 RPKM parameter. To stringently define the somatic-specific genes, we additionally used processed RNA-seq data from ovarian somatic cells (OSCs) (n=4, GSE160860) (41) and filtered the soma-enriched genes using >20 RPKM to select genes that are expressed in OSCs as well as parameter <2 RPKM for early fly embryo (0-2hr, modENCODE) to filter out genes that are expressed in early embryos. This analysis generated a list of 107 germ cell-specifically expressed genes and of 59 somatic cell-specifically expressed genes (Fig.…”
Section: Identification Of Somatic and Germ Cell-specifically Express...mentioning
confidence: 99%
“…Cutup/LC8 (Ctp) has recently been found to be the fourth component of the PICTS/PPNP/SFiNX/Pandas complex (Eastwood et al , 2021; Schnabl et al , 2021). Ctp is ubiquitous and functions in numerous biological processes by dimerizing its interacting complexes to stabilize them (Jespersen & Barbar, 2020).…”
Section: Introductionmentioning
confidence: 99%